Autonomous or controlled self-regulation, that is the question: A self-determination perspective on the impact of commuting on employees' domain-specific functioning. (February 2023) - Gerpott, Fabiola H.; Rivkin, Wladislaw; Unger, Dana
The few studies that have considered psychological processes during the commute have drawn an ambiguous picture, with some emphasizing the negative and others the positive consequences of commuting. Drawing on self-determination theory, we develop a framework that expands on the costs and benefits of commuting for employees' subsequent domain-related functioning at work and home. Specifically, we propose employees' basic needs satisfaction and processes of autonomous and controlled self-regulation as mechanisms that explain how psychological commute characteristics spill over to domain-related functioning through experienced subjective vitality. In doing so, we introduce a taxonomy of psychological commute characteristics and highlight the importance of separating these underlying subjective characteristics from objective aspects of the commuting environment. Our research encourages scholars to conduct within- and between-person studies to examine how the objective commute environment and associated psychological commute characteristics affect employees' self-regulation. Plain Language Summary What happens during the commute does not stay within the boundaries of the commute: Aversive experiences such as being stuck in a traffic jam may spill over to lower engagement in work or home activities. Similarly, positive incidents such as flowing to work uninterruptedly can positively impact subsequent experiences such as flowing (i.e., being fully engaged) when performing tasks at work or at home. How can this be explained? Our article suggests that commuters enter motivational states when going and coming from work. For instance, they feel that everything is going easy and under one's control (autonomous self-regulation) or they feel that the commute is effortful and externally determined (controlled self-regulation). These motivational states influence subjective vitality after the commute, which in turn predicts how employees function at work or at home. Importantly, while objective aspects of the commute environment (for instance, the length of one's commute or one's means of transportation) have an impact on these motivational states, we argue that they do so via psychological commute characteristics perceived by the commuter. We focus on the latter and predict employees' motivational state during the commute in the form of the fulfillment of their basic needs (i.e., feeling autonomous, competent, and related during the commute) as determined by different psychological commute characteristics (decision latitude, psychological stimulation, social characteristics, physical aspects, insecurity). Our work can inspire research that investigates why different employees perceive their commute differently as well as why the same employee may experience different motivational states during their commute from day to day. We end with practical recommendations for communities, organizations, and the commuter themselves.